2009
DOI: 10.1007/s00520-009-0728-x
|View full text |Cite
|
Sign up to set email alerts
|

Illness cognitions in head and neck squamous cell carcinoma: predicting quality of life outcome

Abstract: Goals of workThis paper presents an observational study of the longitudinal effects of cancer treatment on quality of life (QoL) in patients treated for head and neck squamous cell carcinoma (HNSCC), and evaluated the contribution of patients' baseline illness cognitions to the prediction of QoL 2 years after diagnosis.Patients and methodsOne hundred seventy-seven patients eligible for primary treatment for HNSCC completed the Illness Perception Questionnaire-Revised at baseline and the European Organization f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
43
1
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 58 publications
9
43
1
8
Order By: Relevance
“…Furthermore, all QoL aspects may not improve, at least not to the same extent. In the study of Filho et al, despite some symptom scale deterioration, functional scale scores remained high throughout the 3-month follow-up, without significant changes over time, and the overall QoL did not exhibit any significant changes (17); however, the authors commented on significant symptom variability. Melo Filho et al (18) reported loss of physical, social and emotional function and role performance, while Braam et al (16) observed that, compared to baseline, patients reported better emotional functioning and worse social functioning at 12 months, while a better overall health status was reported at 24 months.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, all QoL aspects may not improve, at least not to the same extent. In the study of Filho et al, despite some symptom scale deterioration, functional scale scores remained high throughout the 3-month follow-up, without significant changes over time, and the overall QoL did not exhibit any significant changes (17); however, the authors commented on significant symptom variability. Melo Filho et al (18) reported loss of physical, social and emotional function and role performance, while Braam et al (16) observed that, compared to baseline, patients reported better emotional functioning and worse social functioning at 12 months, while a better overall health status was reported at 24 months.…”
Section: Discussionmentioning
confidence: 92%
“…It is perhaps not surprising that those caring for patients experiencing more symptoms report greater PTSD, as this is likely to entail greater caring demands and, in turn, greater stress. Perceptions of a strong illness identity have been found to predict worse functioning and worse global health in patients with HNC [29], as well as psychological distress in other patient groups [30,31], which may influence caregiver psychological health. The relationship between perceptions of treatment control and PTSD symptoms is more interesting and suggests that having less belief in the benefits of treatment may have implications for caregiver wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment affects the patient through side effects, possible disfigurement, and dysfunction that may result in long-term disability [2,3]. The experience also includes uncertainty due to concerns about the ability to manage daily living, concerns about the efficacy of treatment, and worries about recurrence [4,5]. Head and neck cancer patients experience an array of physical symptoms.…”
Section: Introductionmentioning
confidence: 98%